Method for solution of convolution-type integral equations - P'yanilo, Ya. D. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The spectral method for solution of convolution-type integral equations in the basis of Chebyshev-Laguerre polynomials is reduced to the representation in matrix form. This enables one to construct algorithms of reconstruction of input signals directly from the discrete values of the output signals and to estimate the influence of an input data error on the precision of reconstruction of a signal.